IT Training and Employability of Older Workers - Katrin Schleife (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper empirically analyzes the relationship between firm-provided IT training and the firm?s proportion of older workers. Using data from the ZEW ICT survey of the years 2004 and 2007, the results show that a firm?s IT intensity plays a crucial role: firms intensively using information technologies employ a significantly smaller proportion of older workers than firms that are less IT-intensive. However, higher participation rates of older workers in IT training are related to a larger proportion of older workers within firms. It turns out that this effect is of particular importance in firms that intensively use IT.
Keywords: J24; J21; J14; 330; older workers; IT training; information technologies; Betriebliche Weiterbildung; Computergestütztes Verfahren; Informationstechnik; Ältere Arbeitskräfte; Deutschland